Edukasi pencegahan stunting pada remaja putri serta screening haemoglobin di Dayah Insan Qurani Aceh Besar - Darmawati, Darmawati; Hadijah, Siti; Rahmayanti, Rahmayanti; Fitriana, Fitriana; Andayani, Susi (Politeknik Kesehatan Kemenkes Aceh, 2025)
Adolescent girls are future mothers who will give birth to the next generation of the nation. Currently, the government continues to promote programs aimed at reducing stunting rates to help create a